UJI DIAGNOSTIK FERITIN SERUM UNTUK DETEKSI DEFISIENSI BESI PADA ANAK BALITA - , WINDY SAUFIA APRIYANTI, Prof. Dr. dr. Sutaryo, Sp.A(K) ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Background. Iron deficient is the common cause of anemia worldwide. Most of the children suffer from iron deficient and iron deficiency anemia. Iron deficiency anemia cause great impact to cognitive and motoric development in children until 10 years even though iron therapy has been given. Therefore, early detection of iron deficient is highly recommended. Ferritin serum can be used as an alternative tool in detecting iron deficient. Objective. To assess the diagnostic value of ferritin serum in detecting iron deficient among children below five years. Method. A cross sectional diagnostic test was performed in primary health care at Yogyakarta and Bantul. The inclusion criteria were children in the age of 6 â 59 months. Children who suffered anemia, infection, inflammation and treated with iron therapy and ferritin serum >140 ug/L were excluded. The level of serum receptor transferrin (sTfR) â¥8,2 mg/L used for gold standard in determining iron deficient Diagnostic value count from the level of ferritin serum compared to serum receptor transferrin. Receiver operator curve (ROC) was conducted to choose cut off point of ferritin serum. Result. Prevalence of iron deficient was 32,2% (29/90). The highest prevalence found in the age of 25 â 59 months. Mean hemoglobin level in iron deficient children were lower than healthy children (11,7Â±0,5 and 12,2Â±0,7), mean sTfR level in iron deficient children were higher than healthy children (9,3Â±1,1 and 6,2Â±1,1), there were no significance difference of ferritin serum level between two groups (p=0,228). Sensitivity, specificity and NDP of ferritin serum were 17%, 93% and 56% respectively. Based on ROC, the new cut off point of ferritin serum that was be chosen, was 32,4 ug/L with sensitivity 62,1% and specificity 50,8%. Conclusion. Diagnostic value of ferritin serum was not good enough. Therefore it wasnât able to be an ideal indicator in detecting iron deficient among children below five years.